Pelatihan Menulis Karya Ilmiah Berbasis Pustaka Acuan di SMA Negeri 6 Kota Tangerang Selatan - Julianti, Ulfah; Maemunah, Siti; Triadi, Rai Bagus; Hapsari, Natalia Endah (Jurnal Loyalitas Sosial: Journal of Community Service in Humanities and Social Sciences, 2021)
Abstract: As an education senior High School 6 South Tangerang City is a school that has good integrity in the South Tangerang City area. This is in accordance with the vision and mission of senior High School 6 South Tangerang City that wants to be a religious, superior, creative character and environmentally friendly outcome. So to obtain superior results, need expertise or competence that is mastered by students. One of the expected competencies is to be able to write scientific papers so we provide tridarma of tertiary institutions for the community through training in writing reference-based scientific papers in senior High School 6 South Tangerang City. This kind of training is needed because now students need references to make scientific work that is a mandatory task in Indonesian language lessons. However, problems that arise related to the difficulty of getting reference sources in accordance with the specified theme. So with this training it is expected that students of senior High School 6 South Tangerang City are able to write scientific papers with various sources of reference unreadable not just copy and paste on Google